Dollar Stores, Retailer Redlining, and the Metropolitan Geographies of Precarious Consumption. Issue 4 (7th June 2021) - Shannon, Jerry
Abstract : For the last twenty years, scholarly research has relied primarily on food deserts as a way to frame geographic disparities in access to healthy foods. The results of this research have been empirically mixed, and the term itself has been critiqued as apolitical. Using the alternative framing of retailer redlining, I analyze the rapid growth of dollar stores in twenty-seven metropolitan areas in the United States. Locations for these stores increased by 62 percent nationally during this time period, an expansion that was consistent in all regions of the country. Using descriptive statistics, cross-sectional, and first-difference models, I analyze how neighborhoods' racial makeup was associated with changes in dollar store proximity, controlling for household income, population, and overall retailer density. This analysis shows that proximity to dollar stores is highly associated with neighborhoods of color even when controlling for other factors. This result highlights how the growth of dollar stores and similar spaces designed for economically precarious households both reflect and, potentially, contribute to long histories of racial exclusion.